Editorial - Halilović, Haris (Kriminalističke teme, 2019)
Dear reader, In this English edition of the Criminal Justice Issues – the Journal of Criminal justice and Security we are introducing you three new scientific and one review paper that discuss actual issues in the field of criminology of organized crime and drug trafficking, criminal law and justice. The first is original scientific paper titled “Criminal Justice System’s Response to Corruption-Who is Being Prosecuted and for What?“ Paper examines the criminal justice system’s response to typical corruption offences in order to identify what type of the offenders are been prosecuted and for what type of corruptive offence. The next is original scientific paper titled “How Organized is Organized Crime and Drug Trafficking in Serbia”, which includes normative analysis and empirical research related to suppression of organized crime in Serbia. Third title “Organized Crime and Drug Trafficking in Italy”, also original scientific paper, discusses characteristics of organized criminal groups operating in drug business in Italy. Finally, review paper titled “Criminal Justice Systems’ Response to Drug Trafficking in Bosnia and Herzegovina”, provides an overview of B&H criminal justice systems’ response to drug trafficking discussing the legal framework around illicit production and trafficking in narcotic drugs and data related to reported, prosecuted and adjudicated persons for drug trafficking at state and entity levels. At the end, as many times before, I would like to express my special gratitude to Editorial Board members, authors and peer reviewers who have significantly contributed to the quality of this edition.